Tempest - Ibura, K. (Quill Tree Books, an imprint of HarperCollinsPublishers, 2025)
"After Veronique's parents died, her grandmother raised her on a farm in rural Louisiana. For sixteen years, it's just been Veronique, MawMaw, and an ocean of trees. That's because Veronique has a secret--one MawMaw has warned her she must always keep safe. Veronique has the power to control the wind. But when MawMaw falls ill, Veronique is forced to move to New Orleans to live with family she never knew she had. New Orleans is a far cry from her old quiet life, but Veronique finally gets her chance for a normal life--one with school, friends, and even love. But when her new life threatens her ability to control her powers, she quickly learns that the world is bigger and more dangerous than she'd ever imagined. Veronique must uncover what MawMaw was trying to protect her from before it's too late."-- Provided by publisher.